Drivers of Sectorial Export Earnings’ Performance in Nigeria: A Supply Leading Approach - Anastasia C. Onuorah, Francis Chigozie Okonkwo, Okafor Ikechukwu (International Journal of Advanced Science and Technology, 2020)
The paper investigated the supply leading drivers of sectorial export earrings’performance in Nigeria from 1984 to 2018 using the ARDL Bound test and ECMapproach. The regressed variable is drivers measured by import penetration, economic(trade) openness, foreign direct investment, exchange rate, and inflation rate while theregressor being sectorial export earnings’ performance were disaggregated into oil andnon-oil earnings’ performance based on data derived from the Central Bank of Nigeria(CBN) Statistical Bulletin and World Bank Development index (2018). The result reportedthat only import penetration positively affected oil export earnings in the long run but inthe short run, it adversely affected oil export earnings though FDI inflows passed the testof statistical significance. On the other hand, economic openness and stable inflation ratehave a favourable effect on non-oil export earnings’ performance both on the long andshort run. Again, while exchange rate and FDI inflows have a favourable effect on nonoil export earnings' performance in the short run, in the long-run exchange rate has anegative insignificant effect on oil export earnings' performance. However, only importpenetration passed the test of significance both in the long and short run. To this end, werecommended, reduce tariffs and quota on imported industrial inputs to encouragecontinuous injection of foreign capital into the Nigerian non-oil sector. Again, continuouseffort must be made to ensure that the present inflation and exchange rate is consistentwith her export promotion strategy to ensure that the Nigerian naira is been not overrated.